Parkett : The Parkett series with contemporary artists - ﻿ (Zürich : Parkett-Verlag, 2001)
Table of Content Fabrice Gygi – Reports from the Battle Zone by Claudia Spinelli Tracey Emin Just Be Yourself and Wear A Low Top by Lynn Barber Like a Hole in the Head by Gregor Muir Artist over–and in–the Broadsheets by Robert Preece William Kentridge Doubled Vision – Peering through Kentridge’s Stereoscope by Tom Gunning A Messenger by Susan Stewart Live Cinema & Life in South Afrca by RoseLee Goldberg & William Kentridge Gregor Schneider Negative Spacial Sculpture by Renate Puvogel The Dead House ur by Ulrich Look Jeremy Blake, Insert Katharina Grosse – Painting: A Game of Relations by Rainer Fuchs The Text Is a Work of Art – The Three by Adrian Dannatt Method Masking, Cumulus from America by Christian Rattemeyer From the White Cube to Super Houston, Five Shows in the Portikus, Cumulus from Europe by Daniel Birnbaum Robert Powell – Drawing a Visual Anthropolgy by Michael Oppitz Some Artworks Revisited after September 11, 2001 by Bice Curiger
﻿The cover of this edition of Parkett plays with the pull of introspection. Metaphorically it refers to the art of Tracey Emin, William Kentridge, and Gregor Schneider. Substantial points of convergence are revealed on closer study despite oeuvres that are profoundly dissimilar in approach, provenance, character, and visual idiom. These works direct their attention to elementary concerns: human beings in isolation, surrounded by walls, often naked; the bathroom, the bed, habitation. Also in this issue an Insert by Jeremy Blake. (editorial by publisher)
boek
Keywords: Emin, Tracey; Schneider, Gregor; Kentridge, William